Keterampilan Proses Sains Mahasiswa Pendidikan Fisika STKIP Nurul Huda pada Mata Kuliah Optika - Effendi, Effendi; Rosa Sinensis, Arini; Widayanti, Widayanti; Firdaus, Thoha (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2021)
This study aims to determine the Science Process Skills (KPS) of Physics Education Study Program Students in the Optics Subject. This research uses a descriptive method. The analyzed consists of 9 indicators including observing, clarifying, interpreting data, predicting, hypothesizing, analyzing, planning, experimenting / researching, using tools and materials, applying concepts and communicating. The results showed that the Science Process Skills as a whole obtained an average score of 84.10% in the very good category. Thus it is very clear that KPS Physics Education student STKIP Nurul Huda has excellent skills so that it has a positive effect on the development of student thinking patterns and attitudes which will ultimately have an impact on student success in learning..